Glial Cell Line-Derived Neurotrophic Factor-Loaded CMCht/PAMAM Dendrimer Nanoparticles for Peripheral Nerve Repair - Escobar, A. (2022)
(1) Background: Peripheral nerve injuries represent a major clinical challenge. If nerve ends retract, there is no spontaneous regeneration and grafts are required to proximate the nerve ends and give continuity to the nerve. (2) Methods: GDNF-loaded NPs were characterized physicochemically. For that, NPs stability at different pH’s was assessed, and GDNF release was studied through ELISA. In vitro studies are performed with Schwann cells, and the NPs are labeled with fluorescein-5(6)-isothiocyanate for uptake experiments with SH-SY5Y neural cells. (3) Results: GDNF-loaded NPs are stable in physiological conditions, releasing GDNF in a two-step profile, which is beneficial for nerve repair. Cell viability is improved after 1 day of culture, and the uptake is near 99.97% after 3 days of incubation. (4) Conclusions: The present work shows the efficiency of using CMCht/PAMAM NPs as a GDNF-release system to act on peripheral nerve regeneration.